Urbanismo + ecología: ¿binomio biofílico? estrategias y movimientos internacionales para la planificación de ciudades biofílicas (2017)
The article approaches eco-planning as a strategy to solve some of the problems characteristic of 21st century cities. It analyses urban population growth, the phenomenon of megacities, and the problems they generate. Movements, theories and strategies are reviewed that allow searching for solutions, emphasizing key concepts such as biophilia and biomimesis. Reflections and methodological approaches concerning the possibilities of a more natural territorial planning are raised, In line with the approaches of the green infrastructure or the NBS (Natural Based Solutions), analysing its varied components and the benefits they generate. It is concluded that it is a priority to advance in the study and application of integrative solutions in the line of biophilic cities, since it has the tools and support of many of the agents involved.